Tourism as an Approach to Sustainable Rural Development in Post-Socialist Countries: A Comparative Study of Serbia and Slovenia - Marko D. Petrović (Sustainability, 2017)
The research deals with the sustainable development of the Serbian and Slovenian countryside, under the influence of tourism progress. The article identifies the main rural tourism competitiveness in Serbia and Slovenia, as one of the essential factors of rural development in both countries, analyzing the main contributions and making a series of proposals to guide the future research agenda. The aim of the paper is to clarify around one obviously defined objective—to point out the competitiveness of sustainable rural tourism in typical post-socialist settings. The data for this study were collected using the Integrated Model of Destination Competitiveness to observe Serbian and Slovenian competitiveness in tourism. Determinants were assessed using a survey evaluating four demanding factors and 20 supporting factors, based upon a five-point Likert Scale. The results indicated that the friendliness of residents towards visitors, easy communication between them, together with quality of infrastructure and health facilities show the highest level of statistical correlation. These are the main propositions to start an initiative for the authorities in local communities to actively participate in sustainable rural development. The findings provide tourism stakeholders with relevant respondents’ perceptions pertaining to the tourism development in non-urban areas.